Analyzing the Reality of Financial Technology in the Middle East and North Africa (MENA) Region: Reading of Challenges and Possibilities - sakhri, Abdelwaheb; benali, soumaya (Journal of Research in Finance and Accounting, 2021)
The study aimed to attempt to diagnose the reality of Financial technology in the Middle East and North Africa region, As an innovative alternative to financial services, with the identification of most important obstacles and difficulties, and demonstrating the potential of Financial Technology and opportunities to be exploited. The study concluded that a steady growth of Fintech has been recorded at the International level, but in the Mena region, it has witnessed a variation due to the absence of regulatory and legal frameworks in some countries.